El hombre de los círculos azules - Vargas, Fred; Amo, Helena del; Vargas, Fred. (Madrid : Ediciones Siruela, 2012)
When blue chalk circles begin to appear on the pavement in neighborhoods around Paris, detective Commissaire Adamsberg is alone in thinking that they are far from amusing. As he studies each new circle and the increasingly bizarre objects they contain, he senses the cruelty that lies within whoever is responsible. And when a circle is discovered containing a woman with her throat cut, Adamsberg knows that this is just the beginning.--From publisher's description.
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Adamsberg, Jean-Baptiste -- (Fictitious character) -- Fiction; Police chiefs -- France -- Paris -- Fiction; Murder -- Investigation -- Fiction; Electronic books